2009
DOI: 10.1021/cg900021u
|View full text |Cite
|
Sign up to set email alerts
|

Transport Limited Growth of Zinc Oxide Nanowires

Abstract: Vertical arrays of crystalline zinc oxide (ZnO) nanowires grown on various substrates find applications in dyesensitized and hybrid organic/inorganic bulk-heterojunction solar cells. The ability to grow dense nanowires at high rates and the fundamental understanding of the growth process are important for these applications. Herein, we show that heterogeneous growth of ZnO nanowires on substrates seeded with ZnO nanoparticles in an aqueous solution of methenamine and zinc nitrate is mass transport limited. Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 15 publications
10
78
0
Order By: Relevance
“…The wavelength of the UV light, however, is normally hundreds of nanometers, and therefore the feature size of the pattern is limited to the micrometer range, which gives rise to very dense nanowire arrays growing out of one spot on seeded substrates [77,99]. On a patterned substrate, the growth rate of the nanowires was shown to be inversely proportional to the nanowire density [267,268], simply because the growth nutrient was shared between the competing nanowires. Also, the as-grown nanowires were not straight or uniformly oriented on seeded substrate [77], even though well-controlled ZnO nanowire arrays were grown on GaN substrates using photolithography with one or two nanowires growing out of one spot [269].…”
Section: Photolithographymentioning
confidence: 99%
“…The wavelength of the UV light, however, is normally hundreds of nanometers, and therefore the feature size of the pattern is limited to the micrometer range, which gives rise to very dense nanowire arrays growing out of one spot on seeded substrates [77,99]. On a patterned substrate, the growth rate of the nanowires was shown to be inversely proportional to the nanowire density [267,268], simply because the growth nutrient was shared between the competing nanowires. Also, the as-grown nanowires were not straight or uniformly oriented on seeded substrate [77], even though well-controlled ZnO nanowire arrays were grown on GaN substrates using photolithography with one or two nanowires growing out of one spot [269].…”
Section: Photolithographymentioning
confidence: 99%
“…In the inner part of the array, however, the NRs are rather prismatic. The phenomenon can be ascribed to the transport limited growth as described by Boercker et al in [11]. The measured geometrical parameters are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 73%
“…These images show that the number density of the nanowires can be adjusted by changing the concentration of the ZnO seed solution. Boercker et al suggested two different growth models that can be identified by comparing the height (h) and diameter (R w ) of the ZnO nanowires as a function of their density [20]. The dimensionless Thiele modulus, Φ, which describes the relationship between the diffusion of the Zn precursor and the reaction occurring at the surface of the nanowires, is given by the following equation:…”
Section: Methodsmentioning
confidence: 99%